Analisis Kejadian Malaria pada Pekerja di Pertambangan: Literature Review - Wita Citra Dewi; Hamzah Hasyim; Novrikasari Novrikasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The incidence of malaria has spread throughout the world. Every year more than 500 million people in the world are infected with malaria and more than 1,000,000 people die. Malaria spread factors from various possibilities, such as land clearing, excavation, mining. In addition, climatic factors also affect the distribution of the Anopheles mosquito which causes malaria throughout the world. Several studies were conducted on existing mines in Brazil and Columbia. Prevention of all aspects of possible occurrence of malaria is needed in order to emphasize the number of malaria cases in mining throughout the world, including Indonesia.